Research on intelligent river water quality management system using blockchain-internet of things - Anitha Roy; Jubilant J Kizhakkethottam (Universitas Ahmad Dahlan, 2024)
Each and every living thing needs fresh water to survive. Fresh water is becoming a precious resource as a result of the combined risks of rapid urbanization, pollution, and climatic changes. The quality of the water we drink every day has an impact on our lives, either directly or indirectly. Maintaining the sustainability and health of the environment requires constant attention to water quality. Modern technology makes it possible to gather and analyze data from water distribution networks in order to maximize resources and enhance decision-making for all parties. Despite the enormous global growth of the internet of things (IoT) and blockchain in recent years, their integration is still in its early stages. In this research contains a technological framework that combines blockchain and IoT called B-IoT and aims to reward and incentivize more sustainable water quality management with real-time monitoring and security. IoT is used to monitor water quality in water resources and find any violations. By using blockchain, it is possible to retain the accuracy, reliability, and transparency of the records of breaches. This system will be able to gauge the water’s quality in real-time and allow for the quick identification of any infractions necessary to commit the crime.